Mechanical properties of the patellar tendon in elite volleyball players with and without patellar tendinopathy - Helland, C.; Bojsen-Møller, J.; Raastad, T.; Seynnes, O. R.; Moltubakk, M. M.; Jakobsen, V.; Visnes, H.; Bahr, R. (British Journal of Sports Medicine, 2013)
Background: Although differences in mechanical properties between symptomatic and healthy tendons have been observed for the Achilles tendon, the impact of tendinopathy on patellar tendon mechanics is not fully documented. The aim of the present case-control study was to assess the mechanical properties of the tendon and jump performance in elite athletes with and without patellar tendinopathy.